Non-coding RNAome of RPE cells under oxidative stress suggests unknown regulative aspects of Retinitis pigmentosa etiopathogenesis. Issue 1 (December 2018) - Donato, Luigi; Scimone, Concetta; Rinaldi, Carmela; D'Angelo, Rosalia; Sidoti, Antonina
Abstract The discovery of thousands of non-coding RNAs has revolutionized molecular biology, being implicated in several biological processes and diseases. To clarify oxidative stress role on Retinitis pigmentosa, a very heterogeneous and inherited ocular disorder group characterized by progressive retinal degeneration, we realized a comparative transcriptome analysis of human retinal pigment epithelium cells, comparing two groups, one treated with oxLDL and one untreated, in four time points (1 h, 2 h, 4 h, 6 h). Data analysis foresaw a complex pipeline, starting from CLC Genomics Workbench, STAR and TopHat2/TopHat-Fusion alignment comparisons, followed by transcriptomes assembly and expression quantification. We then filtered out non-coding RNAs and continued the computational analysis roadmap with specific tools and databases for long non-coding RNAs (FEELnc), circular RNAs (CIRCexplorer, UROBORUS, CIRI, KNIFE, CircInteractome) and piwi-interacting RNAs (piRNABank, piRNA Cluster, piRBase, PILFER). Finally, all detected non-coding RNAs underwent pathway analysis by Cytoscape software. Eight-hundred and fifty-four non-coding RNAs, between long non-coding RNAs and PIWI-interacting, were differentially expressed throughout all considered time points, in treated and untreated samples. These non-coding RNAs target host genes involved in several biochemical pathways are related to compromised response to oxidative stress, visual functions, synaptic impairment of retinal neurotransmission, impairment of the interphotoreceptor matrix and blood – retina barrier, all leading to retinal cell death. These data suggest that non-coding RNAs could play a relevant role in Retinitis pigmentosa etiopathogenesis.